"You're in a World of Chaos": Experiences Accessing HIV Care and Adhering to Medications After Incarceration. (September 2015) - Dennis, Alexis C.; Barrington, Clare; Hino, Sayaka; Gould, Michele; Wohl, David; Golin, Carol E.
Abstract : N/A: Most HIV‐infected inmates leave prison with a suppressed viral load; many, however, become disconnected from care and nonadherent to medications during reentry to community life. In this secondary data analysis of focus groups ( n = 6) and in‐depth interviews ( n = 9) with 46 formerly incarcerated HIV‐infected people during reentry, we used an inductive analytic approach to explore the interplay between individual, interpersonal, community, and structural factors and HIV management. Participants described barriers and facilitators to care engagement and adherence at each of these four levels, as well as a milieu of HIV and incarceration‐related stigma and discrimination. The constellation of barriers and facilitators created competing demands and a sense of chaos in participants' lives, which led them to address reentry‐related basic needs (e.g., housing, food) before health care needs. Interventions that simultaneously address multiple levels, including augmenting employment and housing opportunities, enhancing social support, and reducing stigma, are needed.